Strategi Bisnis Teknologi Informasi pada Perusahaan Hitachi, Ltd. - Tri Pudjadi; Achmad Jaya; Defria A. Kiranal; Raedi Rahadian (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Information technology (IT) application for corporate is now a very common thing. It brings many benefits, such as improving business performance, minimizing marketing cost and time, and minimizing the risk in doing business. Hitachi, Ltd. relies on information technology for the company's progress. Various IT strategies performed by Hitachi, Ltd. for improving the quality of their business which one of them is implementing enterprise resource planning (ERP) system of Microsoft Dynamics Navision as its core business application. As a business management software, this system connects many components of the organization by presenting a comprehensive business management functionality-from the financial sector to supply chain. Nevertheless, one of the shortcomings of ERP system is its inefficient schedule solution. Therefore, Hitachi, Ltd. implements a lot of strategies, beside ERP, to survive in the competitive business world of information technology.